Impact of receptor phenotype on nodal burden in patients with breast cancer who have undergone neoadjuvant chemotherapy. Issue 2 (31st July 2017) - Boland, M. R.; McVeigh, T. P.; O'Flaherty, N.; Gullo, G.; Keane, M.; Quinn, C. M.; McDermott, E. W.; Lowery, A. J.; Kerin, M. J.; Prichard, R. S.
Abstract : Background: Optimal evaluation and management of the axilla following neoadjuvant chemotherapy (NAC) in patients with node‐positive breast cancer remains controversial. The aim of this study was to examine the impact of receptor phenotype in patients with nodal metastases who undergo NAC to see whether this approach can identify those who may be suitable for conservative axillary management. Methods: Between 2009 and 2014, all patients with breast cancer and biopsy‐proven nodal disease who received NAC were identified from prospectively developed databases. Details of patients who had axillary lymph node dissection (ALND) following NAC were recorded and rates of pathological complete response (pCR) were evaluated for receptor phenotype. Results: Some 284 patients with primary breast cancer and nodal metastases underwent NAC and subsequent ALND, including two with bilateral disease. The most common receptor phenotype was luminal A (154 of 286 tumours, 53·8 per cent), with lesser proportions accounted for by the luminal B–Her2 type (64, 22·4 per cent), Her2‐overexpressing (38, 13·3 per cent) and basal‐like, triple‐negative (30, 10·5 per cent) subtypes. Overall pCR rates in the breast and axilla were 19·9 per cent (54 of 271 tumours) and 37·4 per cent (105 of 281) respectively. Axillary pCR rates were highest in the Her2‐overexpressing group (27 of 35, 77 per cent) and lowest in the luminal A group (35 of 153, 22·9 per cent) ( P < 0·001). Nodal burden (median number of positive nodes excised) was lower in the Her2‐overexpressing group compared with the luminal A group (0 versus 3; P < 0·001). Conclusion: Her2 positivity was associated with increased rates of axillary pCR and reduced nodal burden following NAC. Abstract : In patients who were initially node positive, Her2 overexpression is associated with increased rates of complete pathological response in the axilla after neoadjuvant chemotherapy. Patients with Her2 receptor amplification could be amenable to less aggressive axillary surgery post NAC. Finding patients who need less invasive surgery